Means of Frequency Expression in Guram Dochanashvili’s Works (based on „The First Garment“) - Pilashvili, Elene ("Intercultural Dialogues" Transactions, 2021)
The article deals with One of the features of the language of Guram Dochanashvili's works is the frequent use of verbs, Dynamic narration of the action process, Which is often loaded with the semantics of multiplicity. Multiplicity with the writer is expressed both through lexical means (Often, Olways, A thousand times, Many times, Several times, Everyday, Tsamdautsum ...), So in the form of a specific sequence (Present, Continuous, Iterative...). All this reveals the great functional-semantic possibilities of the Georgian verb-listener.Observation reveals that the writer's language is characterized by a particularly abundant use of verb-listeners, often burdened with the semantics of multiplicity. The semantic-functional possibilities of the Georgian verb-listener are limitless with the writer. Means of Frequency as a semantic category is very interesting in the language of Guram Dochanashvili's works. It is expressed both in verb forms and in separate words and particles. Sometimes the writer even uses descriptive production to express multiplicity. Means of Frequency are found not only in the para-parasitic construct but also in the hypotaxic construct components of the sentence, both in the main and in the dependent. It is also abundantly proved in the hypotaxic construction containing the time-dependent sentence.